2007
DOI: 10.1590/s0103-64402007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of composites subjected to accelerated aging after curing using either a halogen or a light emitting diode source

Abstract: The purpose of this study was to evaluate, in vitro, the color stability of three composite resins of two different shades (A3 and C3) cured with either a quartz tungsten halogen (QTH) or a light emitting diode (LED) source. Forty specimens (20 x 2 mm) were prepared for each composite (Tetric Ceram ® , Heliomolar ® and Esthet-X ® ), being 20 for each shade. In each group, 10 specimens were light-cured using the QTH unit and 10 with the LED source. The shade of the materials was evaluated before and after submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
2
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 18 publications
2
63
2
12
Order By: Relevance
“…Additionally, the incomplete polymerization has a considerable influence on the color stability [13,15], since no resin-based material can achieve 100% of final curing [23]. The discoloration is commonly attributed to the degeneration of the chemical union between filler particles and resin matrix, and to the solubility of the resin matrix itself and the photo-initiator system [8,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the incomplete polymerization has a considerable influence on the color stability [13,15], since no resin-based material can achieve 100% of final curing [23]. The discoloration is commonly attributed to the degeneration of the chemical union between filler particles and resin matrix, and to the solubility of the resin matrix itself and the photo-initiator system [8,24].…”
Section: Introductionmentioning
confidence: 99%
“…The effect iveness of polymerization depends not only on the chemical composition of the restorative material or the particle size and type, but also on the light-curing devices, including the light spectrum, exposure time and irradiance [24]. It has been observed that resin composites with increased degree of conversion have better mechanical properties, better wear resistance and improved color stability [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…Th e specimens were placed in a two-piece stainless steel matrix with height adjustment, 14 which prevented any contact of the fi nishing and polishing instruments with the matrix surface. Th ese procedures were performed perpendicular to the bipartition marking, 13 with a standardized pressure of 2 kg.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the infl uence of extrinsic factors on color stability, factors related to patient behavior, such as poor oral hygiene and diet based on foods and beverages containing pigments; and those related to the dentist such as fi nishing and polishing procedures are highlighted 10,13,15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, they have several drawbacks: a) The final blue light output is less than 1% of the total energy input; b) QTH lamps have a limited lifespan because light filters degrade with time due to the high operating temperatures and proximity to the halogen bulb. (14)(15)(16) The LEDs system, opposed to QTH light, does not produce visible light through the heating of metal filaments, but through mechanical-quantical effects. (14) The spectral emittance of gallium nitride blue LEDs covers the absorption spectrum of camphorquinone, so that no filters are required in LED light curing units.…”
Section: Introductionmentioning
confidence: 99%